Development trends of big data in modern industries - Jashi, Charita; Urotadze, Ekaterine (Ivane Javakhishvili Tbilisi State University Press, 2023)
Today Big Data is an important and valuable resource worldwide. It is difficult to find a single area of public life that does not depend on fast and reliable data transfer. The dimension of big data covers many aspects, starting from the technological base to the set of economic and business models. The potential of big data in the field of marketing is tremendous, the usage of electronic technologies allows companies to analyze consumer behavior, clearly determine which marketing efforts are successful in order to implement an effective marketing strategy. Many researches approved, that Big data and analytics changing the landscape of various industries. Numerous studies and publications have been provided on this highly relevant issue. The aim of the paper is to discuss the development stages of big data, to explore some views of professionals and Big Data`s specific in many industries. The article is based on numerous scientific works and electronic resources. The paper also discusses regarding managing of Covid-19 pandemic and its consequences
1. Akter, S., & Wamba, S. F. (2019). Big data and disast er management: a systematic review and agenda for future research. Annals of Operations Research, 283(1), 939-959. 2. Austin C., Kusumoto F. (2016) The application of big data in medicine: current implications and future directions. J. Intervent. Card. Electrophysiol. 47(1),51–59. 3. Bamidele A., Emmanuel., Adeniy,A., Kolawole, O.& Ogundokun,R. (2022). Application of big data in COVID-19. Data Science for COVID-19. Volume 2: Societal and Medical Perspectives, pp: 141-149 4. Barutcu M. (2017). Data Analytics for Marketing Revolution, Journal of Media Critiques , 3(11), 163-171. 5. Batistic,,S& Laken, P. (2018) The History, Evolution, and Future of Big Data and its Relationship to Performance in Organizations, Academy of Management Annual Meeting Proceedings 2018(1), pp163 -167. 6. Bosch,V. (2016). Big Data in Market Research: Why More Data Does Not Automatically Mean Better Information", GfK Marketing Intelligence Review, Vol. 8, No. 2 (November), pp. 56-63. 7. Bragazzi, N. L., Dai, H., Damiani, G., Behzadifar, M., Martini, M., & Wu, J. (2020). How big data and artificial intelligence can help better manage the COVID-19 pandemic. International journal of environmental research and public health, 17(9) 8. Buhl, P., Roglinger, D., Moser, D., & Heidemann, D. (2013). Big Data. Business &Information Systems Engineering, 5 (2),pp: 65-69 9. Data Analytics Insight,(2022) How Big Data Is Transforming Industries in Big Ways, https://www.3pillarglobal.com 10. Francesco,R. (2015) Big Data Economics, Big Data Economics Seminar, European Commission/DG Connect/Data Economy Unit,At: Luxembourg. 11. Firican, G. (2020). The History of Big Data, Available from: https://www.lightsondata.com/the-history-ofbig- data/ (Accessed January 27, 2023). 12. Geocases Recommendations (2021). Available from: https://www.geocase.ge (Accessed January 27, 2023). 13. Giri, K. J., & Lone, T. A. (2014). Big data-overview and challenges. International Journal of Advanced Research in Computer Science and Software Engineering, 4(6), 525-529. 14. Hassani, H., Huang, X., MacFeely, S., & Entezarian, M. R. (2021). Big data and the united nations sustainable development goals (UN SDGs) at a glance. Big Data and Cognitive Computing, 5(3), 28. 15. How Big Data Is Transforming Industries in Big Ways, 2022. Available from: https://www.3pillarglobal.com/insights/how-big-data-is-transforming-industries-in-big-ways/ (Accessed January 27, 2023). 16. Jashi, Ch. (2020). The New Context of Marketing in Social Media (Conceptual review). Economics and Business , 1, pp: 152-164. 17. Jashi, Ch., & Urotadze, E. (2020). Marketing Aspect of COVID-19 Epoch. In Proceedings of the 5th International Scientific Conference „Challenges of Globalization in Economics and Business“, Ivane Javakhishvili Tbilisi State University, pp. 397-405. 18. Kar, A. K., & Dwivedi, Y. K. (2020). Theory building with big data-driven research–Moving away from the “What” towards the “Why”. International Journal of Information Management, 54, 102205. 19. Lee, I. (2017). Big data: Dimensions, evolution, impacts, and challenges. Business horizons, 60(3), 293-303. 20. Lukosius, V., & Hyman, M. R. (2019). Marketing theory and big data. The Journal of Developing Areas, 53(4), 217-228. 21. Magoulas, R. (2010) Big Data - Radar - O'Reilly. Available from: http://radar.oreilly.com/2010/01/rogermagoulas- on-big-data.html (Accessed January 27, 2023). 22. Marchesin, A. (2021). The Economics of Big Data: Why, How and What. Available from: https://medium.com/analytics-vidhya/the-economics-of-big-data-why-how-and-what-alessandromarchesin- a57a68606fd6 (Accessed January 27, 2023). 23. Matthews, D. (2020). The Role of Big d Data in Economic Development. Available from: https://www.crayondata.com/big-data-role-economic-development/ (Accessed January 27, 2023). 24. Mayer-Schönberger,V., & Cukier, K. (2013). Big Data: A Revolution That Will Transform How We Live,Work and Think. London: John Murray. 25. Mayer-Schönberger,V., & Ramge,T. (2018). Reinventing capitalism in the age of big data, Hachette UK. 26. Mehta, N., & Shukla, S. (2022). Pandemic analytics: how countries are leveraging big data analytics and artificial intelligence to fight COVID-19?. SN Computer Science, 3(1),1-20. 27. Naik, K., & Joshi, A. (2017, February). Role of Big Data in various sectors. In 2017 International Conference on I-SMAC (IoT in Social, Mobile, Analytics and Cloud)(I-SMAC) (pp. 117-122). IEEE. 28. Palmer, M. (2006). Data is New Oil? Ana Marketing Maestros. Available from: https://ana.blogs.com/maestros/2006/11/data_is_the_new.html (Accessed January 27, 2023). 29. Paoli, A.& Addeo, F. (2020). Big Data to Support Sustainable Development Goals (SDGs), in book: New Metropolitan Perspectives, pp: 738-748 30. Patrinos, H. (2019). World Bank Education Sector. Available from: https://www.worldbank.org (Accessed January 27, 2023). 31. Piccarozzi, M., & Aquilani, B. (2022). The role of Big Data in the business challenge of Covid-19: a systematic literature review in managerial studies. Procedia Computer Science, 200, pp:1746-1755. 32. Pinarbasi, F., & Canbolat, Z. N. (2019). Big data in marketing literature: a Bibliometric Analysis. International Journal of Business Ecosystem & Strategy (2687-2293), 1(2), 15-24. 33. Prevention of Coronavirus Spread in Georgia (2021). Available from: htpp:// www.stopcov.ge (Accessed January 27, 2023). 34. Saidali, J., Rahich, H., Tabaa, Y., & Medouri, A. (2019). The combination between big data and marketing strategies to gain valuable business insights for better production success. Procedia Manufacturing, 32,pp: 1017-1023. 35. Saura, J. R. (2021). Using data sciences in digita l marketing: Framework, methods, and performancemetrics. Journal of Innovation & Knowledge, 6(2), 92-102. 36. Todua, N. (2022). Impact of the COVID-19 Pandemic on Social Media Marketing. In Proceedings of the International Scientific Conference „Covid-19 Pandemic and Economics“, Ivane Javakhishvili Tbilisi State University, pp. 155-160. 37. Todua, N., & Gogitidze, N. (2021). Features of the Use of Digital Marketing in the Banking Sector. The New Economist,16 (3/4), 7-15. 38. Todua, N., & Jashi, Ch. (2021). Paradoxes of Social Marketing in Healthcare (In the Context of COVID-19 Pandemic). In Proceedings of the 6th International Scientific Conference „Challenges of Globalization in Economics and Business“, Ivane Javakhishvili Tbilisi State University, pp:163-168. 39. Todua, N., & Jashi, Ch. (2013). Challenges of Social Marketing. TSU Science, 5, 59-62. 40. Todua,N., &Jashi, Ch. (2022) Opportunities and Challenges of Big Data in Digital Marketing. In Proceedings of the 7th International Scientific Conference „Challenges of Globalization in Economics and Business“, Ivane Javakhishvili Tbilisi State University, pp:203-211. 41. Van, Es,K. &Masson E. (2018). Big Data Histories: An Introduction. Journal for Media History, 21(2), 1-6. 42. Wamba, S. F., Gunasekaran, A., Akter, S., Ren, S. J. F., Dubey, R., & Childe, S. J. (2017). Big data analytics and firm performance: Effects of dynamic capabilities. Journal of Business Research, 70, 356-365.